Communication to the Editor—Allocating Funds to Investment Projects when Returns are Subject to Uncertainty: A Comment - Dyckman, T. R. (Management Science, 1964)
A comment to Cord, J. 1964. A method for allocating funds to investment projects when returns are subject to uncertainty. Management Sci. 10(2, January) 335–341.